Pengembangan Program Studi Diploma 3 Manajemen Pemasaran Melalui Model Struktural Kualitas Kehidupan Kampus - (Jurusan Administrasi Niaga Politeknik Negeri Semarang), Sri Wahyuni (Teknis, 2015)
The successful marketing management program Business Administration State Polytechnic of Semarang must be clever in responding to the stakeholder. Referring to or before, this article is an empirical study on Marketing Management study program. The Election object study is 100 university students in Marketing Management program. Loading technique that sample used in this study is accidental sampling. Data was collected use survey methods by using questionnaires. Technical analysis of using two approaches: Confirmatory factor analysis, in Structural equation model (SEM) with AMOS 22.0, and Regression Weight in SEM. Analysis of data with the approach Confirmatory factor analysis showing a model raised can be accepted. While Regression approaches Weight in 2 of 5 the hypothesis that raised was rejected. Where the hypothesis 3 The impact of satisfaction with facilities study program to the quality of campus life has not proved to be significantly. And The impact of hypothesis 4 Satisfaction with management orientation to the quality of campus life has not proved to be significantly. While formulation question and in this study focused on the quality of campus life, especially question and will support in satisfaction with facilities.Keywords:Â Satisfaction With Lecture Satisfaction, Satisfaction With Facilities,Â Satisfaction With Management Orientation, Quality Of Campus Life And Student Goal Orientation And Behavior